Does Macroprudential Policy Matter For Financial Resilience In Indonesia? - Zainuri Zainuri; Sebastiana Viphindrartin (Journal of International Conference Proceedings, 2022)
Economic problems always negatively impact Indonesian banks' financial resilience because banks, as financial intermediaries, must exercise tight control over all risks that endanger their financial system. The discourse on financial stability became the center of attention of researchers after the 2008 financial crisis because the policy of rapid monitoring of price stability has not been able to create a sustainable economic cycle. On the other hand, there is a phenomenon of the failure of monetary policy to push macroprudential policy into a new policy that can absorb economic risk through banking. This study analyzes the role of banking policy in enhancing Indonesia's financialresilience. The research method used is the ARDL panel. This study finds that the macroeconomic policy mix significantly affects financial resilience in the short and long term.